(untitled) (Swiss Medical Weekly, 2017)
QUESTION UNDER STUDY This pilot study aimed to assess the feasibility, acceptance and costs of an ultrasound scan screening programme for abdominal aortic aneurysms (AAA) in the elderly male population resident in Canton Ticino, Switzerland. METHODS The target population were male patients aged 65–80 years who attended the outpatient clinics of the Lugano Regional Hospital in 2013. The patients showing interest were contacted by phone to verify their eligibility and fix the appointment for the ultrasound scan of the abdominal aorta. Patients with recent examinations suitable for AAA detection were excluded. Aneurysm was defined as an abdominal aorta with sagittal and/or axial diameter ≥30 mm. Patients’ characteristics and study results were presented as descriptive statistics. The chi-squared test was used to compare categorical variables with p <0.05 as a statistical significance threshold. RESULTS 1634 patients received the screening information leaflet and 745 (45.6%) underwent the ultrasound scan. Among the 1091 eligible patients, the acceptance rate was 68.3%. A previously unknown AAA was diagnosed in 31 patients (4.2%, 95% confidence interval 2.8–5.9%). Age and area of residence had a statistically significant impact on patient’s acceptance rate (p <0.05). The mean cost per screened patient was CHF 88. CONCLUSIONS AAA screening of male patients aged 65–80 years is feasible with limited financial and organisational effort. Adherence might be improved by a larger community-based programme and involvement of general practitioners.